1996
DOI: 10.1002/ana.410400617
|View full text |Cite
|
Sign up to set email alerts
|

Muscular dystrophy associated with β‐dystroglycan deficiency

Abstract: beta-Dystroglycan, a 43-kd transmembrane dystrophin-associated glycoprotein, plays an important role in linking dystrophin to the laminin-binding alpha-dystroglycan. alpha-/beta-Dystroglycan is encoded by a single gene on chromosome 3p21 and ubiquitously expressed in muscle and nonmuscle tissues. No known human diseases have been mapped to this locus. Here, we describe the selective deficiency of beta-dystroglycan in a 4-year-old Saudi boy with muscular dystrophy. The patient had a borderline elevation of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…4 B, C ). These types of defects usually lead to dystroglycanopathy in human or mouse models like DG‐null animals, with a clear dystrophic phenotype (54, 55). In particular, signs of necrosis, a switch from fast‐ to slow‐fiber types, fibrosis, regeneration events, inflammation, and increased mitochondrial metabolism are generally detected in muscles.…”
Section: Discussionmentioning
confidence: 99%
“…4 B, C ). These types of defects usually lead to dystroglycanopathy in human or mouse models like DG‐null animals, with a clear dystrophic phenotype (54, 55). In particular, signs of necrosis, a switch from fast‐ to slow‐fiber types, fibrosis, regeneration events, inflammation, and increased mitochondrial metabolism are generally detected in muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The second major receptor for α2‐laminins in the muscle sarcolemma is α‐dystroglycan (Ervasti and Campbell, 1993; Henry and Campbell, 1996; Higuchi et al, 1994; Ibraghimov‐Beskrovnaya et al, 1993; Klietsch et al, 1993; Salih et al, 1996). α‐dystroglycan is a dumbbell‐shaped molecule rich in mucinous sialoglycoconjugate in its neck region that can bind to laminins 1–4, agrin, and perlecan (Brancaccio et al, 1995; Smalheiser and Kim, 1995; Talts et al, 1999).…”
Section: Laminins In Skeletal Muscle and Peripheral Nervementioning
confidence: 99%
“…To date, no disease has been found that is due to primary mutations in dystroglycan, although a mild form of muscular dystrophy associated with a secondary b-dystroglycan deficiency has been described [23]. In addition to LGMD2I, abnormal a-dystroglycan expression has been documented in several forms of congenital muscular dystrophy (CMD), with and without central nervous system (CNS) involvement.…”
Section: Introductionmentioning
confidence: 99%